Distance Learning Program of Teachers’ at Kigali Institute of Education: An expository study - Mukamusoni, Dariya (International Review of Research in Open and Distributed Learning, 2006)
In 2001, a program of distance learning was started within Kigali Institute of Education in collaboration with the Rwanda's Ministry of Education. It is an in-service training program that aims to upgrade in-service secondary school teachers and alleviate the shortage of teachers both in terms of quality and number. This program runs parallel to a pre-service program, also conducted within the Kigali Institute. Academic staff members working in the pre-service program are involved in this distance learning program. After three years, a descriptive qualitative case study was conducted to determine the experiences of academic staff involved in the distance learning program. Purposive and theoretical sampling was used for participants’ identification and inclusion. Individual unstructured interview and focus group discussion was used to gather the data. A qualitative software analysis called NVivo 2, developed by Qualitative Solutions and Research (QSR) International in 2002, was used to compile and analyse the data. Results of the study revealed that faculty members involved in both in-service and pre-service programs face challenges associated with heavy workload. Moreover, the pre-service program is typically prioritized at the expense of the distance learning in-service program. Academic relationships between faculty members and tutors also need to be reinforced. Serving as the critical link between the distance learning in-service program and pre-service departments and faculties, this research also shows that course coordinators play a pivotal role in the smooth operation of the distance learning program.